Towards Achieving Competitive Advantage through the Management of Strategy: Evidence from Smes in Sokoto State - Patrick Ojabo Agbo; Ozovehe Otohinoyi; Eke Tobias (Research Parks Publishers, 2022)
This study assessed the effect of strategic management on the competitive advantage of SMEs in Sokoto State. The study adopted survey research design. A multi-stage sampling technique was used to choose respondents. The sample size of the study was 206. Data collected for the study was analyzed using both descriptive and inferential statistics. Stepwise Multiple Regression was used. The study found that strategy formulation has a substantial negative linear association with competitive advantage of SMEs in Sokoto State. The implementation aspect of strategy management was found to have significant positive linear relationship with the competitive advantage of SMEs in Sokoto State, and strategy evaluation has a substantial positive linear association with SMEs' competitive advantage. The study concluded that the competitive advantage of SMEs in Sokoto State is influenced by strategic management processes. The study recommends that SME owners and policy makers should review their strategic management processes so as to foster the achievement of competitive advantage in Sokoto State.